Belgian hand hygiene campaigns in ICU, 2005–2015. Issue 1 (December 2016) - Fonguh, Sylvanus; Uwineza, Annie; Catry, Boudewijn; Simon, Anne
Abstract Background Healthcare-associated infections (HCAI) are still a major problem especially in most intensive care units (ICU). Incompliance by clinical staff with hand hygiene (HH) increases rates of preventable infections. We report the outcome of the Belgian national hand hygiene campaign from 2005 to 2015 with focus on intensive care units. Methods Using the World Health organisation (WHO) standardised observation roster, trained infection control teams measured adherence to HH guidelines by direct observation. HH opportunities were counted and the actual episodes of HH were scored as no HH, HH with water and soap, or HH with alcohol-based hand rub. Measurements were repeatedly done before and after a one month awareness campaign every second year. Compliance was stratified by indication and by type of healthcare worker, and computed as a percentage of the number of HH episodes with water and soap or with alcohol-based hand rub, divided by the number of opportunities. Results A total of 108, 050 hand hygiene opportunities were observed in ICU during this period. HH compliance increased significantly from 49.6 % before campaign in 2005 to 72.0 % before campaign in 2015. Over the same time frame, post campaign compliance increased from 67.0 to 80.2 %. The number of opportunities observed substantially increased when automated feedback was installed. Conclusions In Belgian intensive care units, hand hygiene compliance is getting improved overtime, though consecutive campaigns with immediate feedback are required to achieve and sustain a high compliance rate.